2016
DOI: 10.1016/j.ejmg.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

A case report of hereditary apolipoprotein A-I amyloidosis associated with a novel APOA1 mutation and variable phenotype

Abstract: Apolipoprotein A-I (apoAI) amyloidosis is a non-AL, non-AA, and non-transthyretin type of amyloidosis associated with mutations in the APOA1 gene inherited in an autosomal dominant fashion. It is a form of systemic amyloidosis, but at presentation, can also mimic localized amyloidosis. The renal presentation generally involves interstitial and medullary deposition of apo A-I amyloid protein. We describe the identification of apo A-I amyloidosis by mass spectrometry in a 52-year old male, with no family history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Many naturally occurring mutations in human apoA-I are associated with reduced plasma HDL levels and hereditary systemic amyloidosis (3). To date, ϳ20 naturally occurring mutations in human apoA-I associated with familial amyloid polyneuropathy have been reported (4,5) in which the majority of the amyloidogenic mutations are clustered in two regions of the N-terminal residues 26 -90 and 154 -178 (4,6,7). Hereditary apoA-I amyloidosis is characterized by deposition of the N-terminal 80 -100-residue fragments of the variant protein as amyloid fibrils in peripheral organs such as heart, liver, kidneys, or gastrointestinal tract, causing organ damage (6,8,9).…”
mentioning
confidence: 99%
“…Many naturally occurring mutations in human apoA-I are associated with reduced plasma HDL levels and hereditary systemic amyloidosis (3). To date, ϳ20 naturally occurring mutations in human apoA-I associated with familial amyloid polyneuropathy have been reported (4,5) in which the majority of the amyloidogenic mutations are clustered in two regions of the N-terminal residues 26 -90 and 154 -178 (4,6,7). Hereditary apoA-I amyloidosis is characterized by deposition of the N-terminal 80 -100-residue fragments of the variant protein as amyloid fibrils in peripheral organs such as heart, liver, kidneys, or gastrointestinal tract, causing organ damage (6,8,9).…”
mentioning
confidence: 99%
“…Acidic intracellular milieu was associated to macrophages activation within inflammatory lesions [40]. As mentioned above, the W50R variant is one of the few exceptions in which apoA-I mutants’ deposits are associated to the glomeruli [13][41]. The extracellular matrix (ECM), especially the proteoglycans (PGs) have diverse biologic functions, including binding of growth factors and regulation of collagen fibrillogenesis [42], and their composition is tissue specific [43].…”
Section: Discussionmentioning
confidence: 99%
“…As a difference from other hereditary amyloidosis, in which renal failure occurs mainly due to glomerular protein deposits [9][10], apoA-I associated disease is mostly characterized by amyloid retention in the medullary interstitium and/or vasculature, which is probably a reason for its misdiagnosis [11][12]. Only rare exceptions were observed within a few mutants including W50R, in which amyloid deposits were found in glomeruli, either confined [13], or expanded to medulla. Previous works from our and other groups have demonstrated that the single point mutations described for apoA-I decrease the marginal protein stability and elicit the tendency to aggregate; even though the conformational shift in the variants is usually subtle under physiological pH and low concentration, it could also induce alterations of the binding to ligands or the eliciting of pro-inflammatory cellular events [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report of the mutation in Chinese Han population, and the previous reports were from a Jewish man and a Danish man. [ 5 , 28 ] The major clinical manifestations of the 3 cases include renal amyloidosis and low plasma levels of ApoA-1 and HDL. This may indicate that the Trp74Arg mutation can result in dysfunctional and amyloidogenic ApoA-1 proteins, which mainly targets kidney.…”
Section: Discussionmentioning
confidence: 99%